2017
DOI: 10.4238/gmr16019363
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 desensitizes flow-induced responses in osteoblasts

Abstract: ABSTRACT. Bone desensitization after mechanical loading is essential for bone to adapt to its mechanical environment. However, the desensitization mechanism is unknown. Previous studies suggest that G protein-coupled receptors (GPCRs), including P2Y and parathyroid hormone receptors, play important roles in osteoblast mechanobiology. Thus, for the present research, we examined the role of G protein-coupled receptor kinase 2 (GRK2) in osteoblast desensitization after exposure to mechanical stimulation. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…After subjected to oscillatory fluid flow for 5 minutes, MC3T3-E1 osteoblast may take up to 120 minutes to completely recover its sensitivity to respond to another oscillatory fluid flow according to our previous experiments [ 28 ]. In this study, MC3T3-E1 cells were treated with or without PTH for 30 minutes after first fluid flow stimulation, then exposed to second fluid flow stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After subjected to oscillatory fluid flow for 5 minutes, MC3T3-E1 osteoblast may take up to 120 minutes to completely recover its sensitivity to respond to another oscillatory fluid flow according to our previous experiments [ 28 ]. In this study, MC3T3-E1 cells were treated with or without PTH for 30 minutes after first fluid flow stimulation, then exposed to second fluid flow stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Since both PTH receptor and P2Y2 receptor are GPCRs, they can be desensitized by GPCR kinases (GRKs). We have previous demonstrated that GRKs may be involved in fluid flow-induced osteoblast desensitization [ 28 ]. If PTH receptors are desensitized by the same GRK as P2Y2 receptors, then the administration of PTH may lead to recruitment of GRK to PTH receptors.…”
Section: Discussionmentioning
confidence: 99%